Altered olfactory responses in Fmr1 KO mice - Jan Tuma; Amtul-Noor Rana; Teena Philip; Jeong Ben Park; Hye Young Lee (Scientific Reports)
Abstract Fragile X syndrome (FXS) is a neurodevelopmental disorder oftentimes associated with abnormal social behaviors and altered sensory responsiveness. It is hypothesized that the inappropriate filtering of sensory stimuli, including olfaction, can lead to aberrant social behavior in FXS. However, previous studies investigating olfaction in animal models of FXS have shown inconsistent results. Here, we found that Fmr1 knock-out (KO) mice, a mouse model of FXS, showed increased sniffing duration for non-social odors during their first exposure. Additionally, while wild-type (WT) males demonstrated differences in behavioral patterns between non-social odors while Fmr1 KO males did not show such distinction. We also showed that Fmr1 KO males spent significantly less time sniffing female urine odor compared to WT males. Moreover, we found an increased volume of the olfactory bulb in Fmr1 KO males. Overall, our findings suggest that the Fmr1 KO mice demonstrate atypical olfactory behaviors as well as structural changes in the olfactory bulb.